Cardiac memory T wave frequency as an electrocardiographic surrogate for structural myocardial alteration in the hearts of dorpersheep - Papendorp, D.H. (University of Pretoria, 2013)
Thesis (PhD (Human Physiology))--University of Pretoria, 2006.